An O-Glycosyltransferase Promotes Cell Adhesion during Development by Influencing Secretion of an Extracellular Matrix Integrin Ligand. - Zhang, L.; Tran, D.T.; Ten Hagen, K.G. (Journal of Biological Chemistry, 2010)
Protein secretion and localization are crucial during eukaryotic development, establishing local cell environments as well as mediating cell interactions, signaling, and adhesion. In this study, we demonstrate that the glycosyltransferase, pgant3, specifically modulates integrin-mediated cell adhesion by influencing the secretion and localization of the integrin ligand, Tiggrin. We demonstrate that Tiggrin is normally O-glycosylated and localized to the basal matrix where the dorsal and ventral cell layers adhere in wild type Drosophila wings. In pgant3 mutants, Tiggrin is no longer O-glycosylated and fails to be properly secreted to this basal cell layer interface, resulting in disruption of integrin-mediated cell adhesion in the wing. pgant3-mediated effects are dependent on enzymatic activity, as mutations that form a stable protein yet abrogate O-glycosyltransferase activity result in Tiggrin accumulation within the dorsal and ventral cells comprising the wing. Our results provide the first in vivo evidence for the role of O-glycosylation in the secretion of specific extracellular matrix proteins, thus altering the composition of the cellular "microenvironment" and thereby modulating developmentally regulated cell adhesion events. As alterations in cell adhesion are a hallmark of cancer progression, this work provides insight into the long-standing association between aberrant O-glycosylation and tumorigenesis.